2018
DOI: 10.1371/journal.pone.0194454
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of underweight, overweight and obesity and their related socio-demographic and lifestyle factors among adult women in Myanmar, 2015-16

Abstract: BackgroundThe aim of the study was to estimate the prevalence of underweight and overweight or obesity and their socio-demographic and lifestyle factors in a female adult population in Myanmar.Material and methodsIn a national cross-sectional population-based survey in the 2015–16 Myanmar Demographic and Health Survey, 12,160 women aged 18–49 years and not currently pregnant completed questionnaires and anthropometric measurements. Nutritional status was determined using Asian body mass index cut-offs: underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 22 publications
16
35
0
1
Order By: Relevance
“…These are known facts that factors such as rapid urbanization, sedentary lifestyles, consumption of junk food, and high-energy drinks are concurrently contributing to a surge in rates of overweight and obesity in LMICs, and Nepal is not an exception to it. Our estimates are comparable with previous studies from other South Asian nations, which reported a higher prevalence of overweight and obesity in urban areas than in the rural [21,22,35]. The consequences of obesity, followed by its longterm health conditions such as heart disease, hypertension, stroke, and diabetes, would be detrimental to the fragile public health systems in LMICs [36], including in Nepal [37].…”
Section: Discussionsupporting
confidence: 86%
“…These are known facts that factors such as rapid urbanization, sedentary lifestyles, consumption of junk food, and high-energy drinks are concurrently contributing to a surge in rates of overweight and obesity in LMICs, and Nepal is not an exception to it. Our estimates are comparable with previous studies from other South Asian nations, which reported a higher prevalence of overweight and obesity in urban areas than in the rural [21,22,35]. The consequences of obesity, followed by its longterm health conditions such as heart disease, hypertension, stroke, and diabetes, would be detrimental to the fragile public health systems in LMICs [36], including in Nepal [37].…”
Section: Discussionsupporting
confidence: 86%
“…The high prevalence of overweight/obesity is associated with an increased burden from NCDs in Myanmar, as shown by recent evidence 7 38. An unintended consequence of the continuing economic development of the country is the increasing preference for a sedentary lifestyle and obesogenic food, which, in turn, is raising the burden of overweight/obesity.…”
Section: Discussionmentioning
confidence: 98%
“…In 2015–2016, the first Myanmar Demographic and Health Survey (MDHS) was conducted using a nationally representative sample across the country 6. The survey found a high prevalence of overweight and obesity among women of reproductive age 7…”
Section: Introductionmentioning
confidence: 96%
“…The consequences of overweight and obesity on women are critical, particularly during pregnancy which is accompanied with numerous adverse outcomes ( 13 , 14 ). Obesity is a risk factor for numerous NCDs including cardiovascular diseases, stroke, and various forms of cancer resulting to illness and premature death ( 15 ). The recent shift in nutritional patterns has posed public health problems such as increase in the prevalence of overweight and obesity ( 16 ).…”
Section: Introductionmentioning
confidence: 99%